2010
DOI: 10.1124/jpet.110.169391
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Electrocardiographic and Cardiac Ion Channel Effects of (−)-Epigallocatechin-3-Gallate, the Main Catechin of Green Tea

Abstract: Epigallocatechin-3-gallate (EGCG) is the major catechin found in green tea. EGCG is also available for consumption in the form of concentrated over-the-counter nutritional supplements. This compound is currently undergoing clinical trials for the treatment of a number of diseases including multiple sclerosis, and a variety of cancers. To date, few data exist regarding the effects of EGCG on the electrophysiology of the heart. Therefore, we examined the effects of EGCG on the electrocardiogram recorded from Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
7
25
3
Order By: Relevance
“…At these pharmacological concentrations, the actions of EGCG are mediated by selective activation of ryanodine receptor type 2 (RyR2) and inhibition of plasmalemma Ca 2ϩ fluxes via the Na ϩ -Ca 2ϩ exchanger (NCX), with negligible influence on Ca 2ϩ -ATPase (SERCA2), Na ϩ -H ϩ exchanger, and Na ϩ -K ϩ -ATPase. Previous work has shown that nanomolar EGCG has also no effect on L-type Ca 2ϩ current in ventricular myocytes (Kang et al, 2010). These coordinated actions of EGCG result in a net shift of Ca 2ϩ transport during the cardiac cycle away from the plasma membrane to the energetically more favorable sarcoplasmic reticulum (SR) Ca 2ϩ transport, which may represent a novel therapeutic strategy for increasing cardiac contractility in patients with heart failure.…”
Section: (ϫ)-Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
See 1 more Smart Citation
“…At these pharmacological concentrations, the actions of EGCG are mediated by selective activation of ryanodine receptor type 2 (RyR2) and inhibition of plasmalemma Ca 2ϩ fluxes via the Na ϩ -Ca 2ϩ exchanger (NCX), with negligible influence on Ca 2ϩ -ATPase (SERCA2), Na ϩ -H ϩ exchanger, and Na ϩ -K ϩ -ATPase. Previous work has shown that nanomolar EGCG has also no effect on L-type Ca 2ϩ current in ventricular myocytes (Kang et al, 2010). These coordinated actions of EGCG result in a net shift of Ca 2ϩ transport during the cardiac cycle away from the plasma membrane to the energetically more favorable sarcoplasmic reticulum (SR) Ca 2ϩ transport, which may represent a novel therapeutic strategy for increasing cardiac contractility in patients with heart failure.…”
Section: (ϫ)-Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…It is therefore likely that results from in vitro experiments at high concentrations could mask more specific mechanisms by which EGCG exerts its biological actions at pharmacologically relevant doses (Ͻ10 M). Recent reports suggest that EGCG increases cardiac contractility at low micromolar concentrations (1-5 M) (Lorenz et al, 2008) without altering ECG parameters and cardiac ion channels (Kang et al, 2010). The molecular mechanisms responsible for the positive inotropic effect of EGCG remain unclear.…”
Section: (ϫ)-Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…For example, calcium influx through L-type calcium channels regulates the threshold of cAMP-induced StAR gene expression, so that blocking the L-type calcium channels reduced the threshold and enhanced StAR gene expression in Leydig cells (Pandey et al, 2010). There is a group of natural flavonoids that are able to block the L-type calcium channels, such as genistein (Belevych et al, 2002), daidzein (Yokoshiki et al, 1996), equol (Liew et al, 2003) and epigallocatechin-3-gallate (EGCG) (Kang et al, 2010). The steroidogenic effects of the flavonoids in this group were described (Yu et al, 2010).…”
Section: Potential Application Of Natural Flavonoids In Delaying the mentioning
confidence: 99%
“…The interest in polyphenols is related to their well-known antioxidant activities which are reported to have positive effects on human health, due to their presence in dietary sources such as fruits, vegetables, wine, spices and herbs [16]. Green tea, prepared from the leaves of Camellia sinensis, is one of the popular beverages that are reported to have a number of beneficial health effects, including anti-inflammatory, anti-thrombotic and anticancer activities [12]. Green tea is rich in polyphenolic compounds, known as catechins, that are responsible for the physiological activity of green tea and its extracts.…”
Section: Introductionmentioning
confidence: 99%